When herpes simplex virus encephalitis meets antiviral innate immunity - Zhang, Linhai; Zhang, Lijia; Li, Fangjing; Liu, Wanyu; Tai, Zhenzhen; Yang, Juan; Zhang, Haiqing; Tuo, Jinmei; Yu, Changyin; Xu, Zucai (Frontiers in Immunology, 2023)
Herpes simplex virus (HSV) is the most common pathogen of infectious encephalitis, accounting for nearly half of the confirmed cases of encephalitis. Its clinical symptoms are often atypical. HSV PCR in cerebrospinal fluid is helpful for diagnosis, and the prognosis is usually satisfactory after regular antiviral treatment. Interestingly, some patients with recurrent encephalitis have little antiviral effect. HSV PCR in cerebrospinal fluid is negative, but glucocorticoid has a significant effect after treatment. Specific antibodies, such as the NMDA receptor antibody, the GABA receptor antibody, and even some unknown antibodies, can be isolated from cerebrospinal fluid, proving that the immune system contributes to recurrent encephalitis, but the specific mechanism is still unclear. Based on recent studies, we attempt to summarize the relationship between herpes simplex encephalitis and innate immunity, providing more clues for researchers to explore this field further.